2020
DOI: 10.9779/pauefd.567616
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Yedinci ve Sekizinci Sınıf Öğrencilerinin Cebirsel İfadeler Konusundaki Başarı Performanslarının İncelenmesi

Abstract: Bu araştırmanın amacı, ortaokul yedinci ve sekizinci sınıf öğrencilerinin cebirsel ifadeler konusundaki başarı performanslarını incelemektir. Araştırmada tarama yöntemi kullanılmıştır. Araştırmanın çalışma grubunu Afyonkarahisar ilinde yedinci ve sekizinci sınıfta öğrenim gören toplam 180 ortaokul öğrencisi oluşturmaktadır. Veri toplama aracı olarak 7 alt boyuttan oluşan 28 soruluk çoktan seçmeli bir cebir testi kullanılmıştır. Bu araştırmada verilerin analizinde SPSS 17.0 paket programı kullanılmış, değişkenl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
2
0
3
Order By: Relevance
“…When the literature is examined, it has been shown in many studies conducted at different grade levels that students have a variety of errors in the usage and meaning of the letters in algebraic expressions (Akkaya & Durmuş, 2006;Bayar, 2007;Baysal, 2010;Carraher & Schliemann, 2007;Erdem, 2013;Ertekin, 2002;Kieran, 1992;Linchevski, 1995;Perso, 1992;Yenilmez & Avcu, 2009), and they have misconceptions, and they have difficulties in transitioning from arithmetic to algebra (Akkan & Baki, 2016;Akkan et al, 2012;Birgin & Demirören, 2020;Cai & Knuth, 2011;Gülpek, 2006;Kaya, 2017;Kieran & Chalouh, 1993;Linchevski & Herscovics, 1996). In their study conducted with 6-8th grade students, Akkaya and Durmuş (2006) have found that the students had difficulty in perceiving the letters in algebraic representation; they have perceived the letters used in algebraic representation as a numerical position as in the alphabetical order; they perceive letters as digit values and think that letters cannot take any other value than numbers; students do not take into account the order of operations when using letter expressions and parentheses while making transactions; they perceive letters as labels for words.…”
Section: Purpose and Significancementioning
confidence: 99%
See 3 more Smart Citations
“…When the literature is examined, it has been shown in many studies conducted at different grade levels that students have a variety of errors in the usage and meaning of the letters in algebraic expressions (Akkaya & Durmuş, 2006;Bayar, 2007;Baysal, 2010;Carraher & Schliemann, 2007;Erdem, 2013;Ertekin, 2002;Kieran, 1992;Linchevski, 1995;Perso, 1992;Yenilmez & Avcu, 2009), and they have misconceptions, and they have difficulties in transitioning from arithmetic to algebra (Akkan & Baki, 2016;Akkan et al, 2012;Birgin & Demirören, 2020;Cai & Knuth, 2011;Gülpek, 2006;Kaya, 2017;Kieran & Chalouh, 1993;Linchevski & Herscovics, 1996). In their study conducted with 6-8th grade students, Akkaya and Durmuş (2006) have found that the students had difficulty in perceiving the letters in algebraic representation; they have perceived the letters used in algebraic representation as a numerical position as in the alphabetical order; they perceive letters as digit values and think that letters cannot take any other value than numbers; students do not take into account the order of operations when using letter expressions and parentheses while making transactions; they perceive letters as labels for words.…”
Section: Purpose and Significancementioning
confidence: 99%
“…Bu durum matematik derslerinde daha çok cebirsel ifadeler konusunda aritmetik işlem boyutunun ön plana çıkarıldığı, görsel ve cebirsel ifadelerin farklı gösterim türleri arasında geçişlere yeterince yer verilmediği şeklinde yorumlanabilir. Nitekim yapılan bazı araştırmalar (Akkaya ve Durmuş, 2006;Birgin ve Demirören, 2020;Macgregor ve Stacey, 1997;Perso, 1992) öğrencilerin daha çok görsel ifade içeren cebirsel problemlerde daha başarısız olduklarını ortaya koymaktadır. Bu yönüyle bu araştırmanın bulgularını destekler niteliktedir.…”
Section: Tartışma Ve Sonuçunclassified
See 2 more Smart Citations
“…For this reason, it is emphasized that conceptual and transactional knowledge should take place in mathematics teaching in a balanced way (Baki, 1998;Baki & Kartal, 2004;Soylu & Aydın, 2006). By balancing conceptual and transactional knowledge, it becomes easier for students to reveal highlevel thinking skills necessary for understanding mathematics, to make assumptions, generalize and make connections between subjects (Birgin & Gürbüz, 2009). Realization of conceptual learning has an important place in mathematics education in terms of both more permanent knowledge and the formation of a more meaningful learning situation.…”
mentioning
confidence: 99%